Radiation pneumonitis after palliative radiotherapy in cancer patients with interstitial lung disease. (August 2021) - Okumura, Masayuki; Hojo, Hidehiro; Nakamura, Masaki; Hiyama, Takashi; Nakamura, Naoki; Zenda, Sadamoto; Motegi, Atsushi; Hirano, Yasuhiro; Kageyama, Shun-Ichiro; Parshuram, Raturi Vijay; Fujisawa, Takeshi; Kuno, Hirofumi; et al.
Highlights: Radiation pneumonitis (RP) is an adverse event of radiotherapy (RT). Interstitial lung disease (ILD) is known as a risk for RP after definitive RT. We retrospectively investigated whether ILD is a risk for RP after palliative RT. Fatal RP occurred in 10% of ILD patients who received palliative thoracic RT. ILD pattern was a significant predictive factor for severe RP. Abstract: Purpose: The risk of radiation pneumonitis (RP) after palliative radiotherapy (RT) in cancer patients with interstitial lung disease (ILD) remains unclear. This study aimed to investigate the incidence, severity, and predictive factors of RP among patients with ILD who received palliative RT. Methods and materials: The medical records of cancer patients with ILD who received palliative RT involving a lung field between January 2008 and December 2019 were retrospectively reviewed. Screening for ILD was performed by using the ICD-10 diagnosis code, and the ILD was evaluated on the basis of pretreatment computed tomography (CT). RP was scored using Common Terminology Criteria for Adverse Events, version 5.0. Associations between both clinical and dosimetric factors and RP were assessed by univariate and multivariate analyses. Results: Sixty-two patients were included in the analysis. The median prescribed physical dose of RT was 25 Gy (range, 6–40 Gy). The RP was graded 1, 2, 3, 4, and 5 in 6 (10%), 3 (5%), 1 (2%), 2 (3%), and 6 (10%) patients, respectively. The median time to onset of grade 3 or more RP (≥Gr3 RP) was 39 days (range, 10–155). The results of the multivariate analysis indicated that ILD pattern was a significant predictive factor for ≥Gr3 RP (odds ratio, 12.0; 95% confidence interval, 1.02–1664; P < 0.05). Conclusions: RT involving a lung field, even when prescribed with palliative intent, should be administered carefully to ILD patients. Evaluation of the ILD pattern on pretreatment CT images may be of help in determining whether to perform RT.